Tine weeding rake [library of things] (Johnny's Garden Seeds, 2019)
"Tine weeding is a form of blind cultivation that focuses on removing weeds when they are at their most vulnerable state: the white thread stage. If done properly, tine weeding can remove a gret number of weeds from your garden before they take up nutrients and water necessary for your crops. "-- instruction sheet